Wein, Erwin J., y Opificius, Ruth: 7000 Jahre Byblos. Ed. Hans Carl. 56 pp. y 68 láminas fotográficas. Nuremberg, 1963. - Schobinger, Juan (1965)
Fil: Schobinger, Juan. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras